ENTREPRENEURIAL SUPPLY CHAIN MANAGEMENT COMPETENCE: PREDICTORS OF WORK MOTIVATION ADVOCATE - Prayetno, Sugeng; Ali, Hapzi (International Journal of Supply Chain Management, 2020)
Abstract? This research paper investigates the impact of five factors indirectly on entrepreneurial Supply chain management competence and two other factors SCM strategies and performance of firm. Innovativeness Orientation, Risk-taking characteristics, Pro activeness, relational capital, coordination capability, SCM strategies and performance are the multi-dimensional factors effecting entrepreneurial SCM competence in Advocate Performance Analysis.  This study aims to analyze the influence of advocate's work motivation on advocate performance partially, knowledge of entrepreneurship of advocate on partial advocate of performance, independence of advocate work on partial advocate performance, and advocate work motivation, knowledge of entrepreneurship supply chain of advocate and independency of advocate work simultaneously. The population of this research is Law Firms that exist in all the Greater Jakarta area. While the sample is 25 percent of the existing Law Firm, then Obtained 123 Law Firms. In general, there are two divisions of the Legal Firm namely division of litigation and non-litigation division. Thus Spake Obtained the number of units observed are as follows: 2 x 123 = 246 units. The research is Quantitative analysis method using multiple linear regression analysis, Followed by determination analysis (R Square) partial hypothesis testing (t test) and simultaneous (F test) with alpha 5 percent (0.05). Prior to further analysis, the data quality and classical assumption test were conducted. Analytical tools using SPSS version 23.0 for Windows. The result of the research shows that the work motivation of advocate has an effect on the performance of advocate partially, the knowledge of entrepreneurship supply chain of the advocate has an effect on the performance of the advocate partially, the advocate's independency has an effect on the advocate's performance, and the advocate's work motivation, knowledge of entrepreneurship and independency of advocate influence on the advocate's performance simultaneously at the advocate's office Law Firm in Jabodetabek Data quality and classical assumption test were conducted.